1999
DOI: 10.1023/a:1006233700194
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Ixodes ricinus ticks infected with Borrelia burgdorferi sensu lato were numerous on the edges of paths and roads in a recreational park in south-western Ireland. The abundance of ticks at different sites was related to the presence of deer, but a negative relationship was shown between tick abundance and tick infection rates. This is thought to be due to the deposition of large numbers of uninfected ticks by deer, which are apparently not good reservoir hosts of B. burgdorferi s.l. Blood meal analysis only det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 24 publications
4
27
1
Order By: Relevance
“…DNA of more than one host was detected in 10.7% of single nymphs, in agreement with previous studies [21, 22, 49]. While it has been suggested that mixed blood meals are the result of contamination, this is unlikely in our study since all DNA extraction and amplification controls were negative.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…DNA of more than one host was detected in 10.7% of single nymphs, in agreement with previous studies [21, 22, 49]. While it has been suggested that mixed blood meals are the result of contamination, this is unlikely in our study since all DNA extraction and amplification controls were negative.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, mixed blood meals were unambiguous, as hosts were identified in independent reactions with different host-group specific primer sets. Although multiple host blood meals run contrary to the widely held view that I. ricinus takes one blood meal from a single host per life stage (see Background), Gray et al [49] also observed the occasional collection of semi-engorged larvae by blanket dragging, suggesting that multiple blood meals are occasionally necessary for full engorgement, after voluntary drop off, involuntary interrupted feeding, or unsuccessful full attachment. We observed that many different host combinations are possible (see Table 4): two rodents, rodent and bird, rodent and carnivore, rodent and ungulate, etc., presumably not only resulting in mixed blood meals, but also promoting multiple pathogen transmission between hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from France, Ireland and Austria showed prevalence of B. burgdorferi ( s.l .) in small mammal species ranging from 2.3 to 24% [6668]. The infection level in small mammals in the current study was slightly higher than these obtained in earlier European studies (31.3%).…”
Section: Discussioncontrasting
confidence: 68%
“…This suggestion is supported by previous studies in Ireland that also found bird-associated Borrelia genospecies to be the most common Borrelia infections present in questing ticks and that wood mice were rarely infected with B. burgdorferi s.l. (Kirstein et al 1997;Gray et al 1999Gray et al , 2000.…”
Section: Discussionmentioning
confidence: 99%